PENDAMPINGAN PENGEMBANGAN USAHA LAUNDRY BERBASIS BREAK EVEN POINT DAN DRYSHIFT TECHNOLOGY - Sudirman, Sudirman; Ruslang T, Ruslang T; Usman, Usman (Media Literasi Indonesia, 2025)
The laundry business in urban areas, including Parepare City, has seen rapid growth over the past five years, but many MSMEs still rely on traditional drying methods and non-data-driven cost management. This situation leads to unstable operations and intuitive business decisions. This Community Service (PKM) activity aims to improve cost management skills through Break Even Point (BEP) training and encourage operational optimization by introducing modern drying technology. The activity was held at Netla Laundry, Jln. Lingkar Lanyer Parepare, involving owners and employees. The methods used included counseling, interactive discussions, demonstrations, and technical assistance based on real business data. The activity results showed a significant increase in participants' understanding of cost structures, BEP calculations, and their application in determining prices and assessing investment feasibility. Participants also understood the advantages of modern drying technology over solar-based methods, including time efficiency and service stability. In conclusion, this assistance successfully strengthened Netla Laundry's managerial and operational capacity, as well as providing a foundation for technological transformation and increasing business competitiveness.